The Griffin Plan for Shanghai, 1904-1906 - Weirick, James (International Planning History Society Proceedings, 2018)
An event in Yokohama in January 1906 – the accidental death of the Chinese trade commissioner to Japan, Huang Kaijia (1860-1906)– seems to have ended one of the most intriguing city planning ventures of the early modern era. Two years previously, as Imperial Vice Commissioner to the St Louis Exposition, Huang Kaijia was almost certainly the ‘delegate from the Chinese government’ who commissioned the design of a ‘new city at Shanghai’ from the American architect and landscape architect Walter Burley Griffin (1876-1937). This paper reviews the testimony emanating from Griffin and his colleagues on which the claim for a Shanghai city plan from 1904-1906 is based; the modernising impulses in Shanghai at the time; and the broader context of ‘New China’ reforms initiated by the Qing Dynasty in the first decade of the twentieth century. From the available descriptions, the following details of the proposal can be established. First, the project was a Chinese initiative, not a ‘colonial’ venture associated with the Foreign Settlements. Second, the proposal involved ‘a modern city on a new site’ located ‘a few miles’ from the traditional walled city. Third, the project was conceived as an alternative to the ‘narrow streets, swarming tenements and insanitary areas’ of the ‘old city’ – and, indeed, included the proposal to ‘abandon the old city.’ Fourth, Griffin ‘drew the plans for the new Shanghai in detail.’ Based on archival research, critical review of contemporary newspaper accounts and recent scholarship on the ‘tradition vs modernity’ debate in Chinese historiography, the paper seeks to address the question, what does the fragmentary evidence of the ‘Griffin Plan for Shanghai’ tell us about innovation and change in urban thinking before the Chinese of revolution of 1911; the continuity of ideas across the revolutionary divide; and the distinctive fusion of modernity and poetic power in the successor to the Shanghai scheme in the Griffin oeuvre, the winning entry in the Australian Federal Capital competition of 1911-1912.